2001
DOI: 10.1097/00007632-200107150-00004
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Macrophage Infiltration of Herniated Disc Tissue on the Production of Matrix Metalloproteinases Leading to Disc Resorption

Abstract: These results suggest that peripheral blood mononuclear cells infiltrating extruded discs may secrete a variety of biologic materials capable of further recruiting monocytes into herniated discs in an autocrine fashion. Disc cells stimulated with cytokines showed enhanced production of matrix metalloproteinases, which might play an important role in spontaneous regression of disc materials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
82
0
3

Year Published

2006
2006
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 129 publications
(87 citation statements)
references
References 25 publications
2
82
0
3
Order By: Relevance
“…Subsequently, various inflammatory chemical factors secreted from herniated NP, including tumor necrosis factor (TNF)-α (Weiler et al, 2005;Le Maitre et al, 2007), interleukin (IL)-1β (Le Maitre et al, 2007) and nitric oxide (NO) (Katsuno et al, 2008), have been implicated as causes of sciatica (McCarron et al, 1987;Geiss et al, 2007). Further, the production of matrix metalloproteinases (MMPs) has been implicated in the resorption of the herniated NP (Doita et al, 2001). Bobechko and Hirsh (1965) and Gertzbein et al (1975) reported that herniated NP tissue is recognized as a foreign antigen that induces an autoimmune response producing inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequently, various inflammatory chemical factors secreted from herniated NP, including tumor necrosis factor (TNF)-α (Weiler et al, 2005;Le Maitre et al, 2007), interleukin (IL)-1β (Le Maitre et al, 2007) and nitric oxide (NO) (Katsuno et al, 2008), have been implicated as causes of sciatica (McCarron et al, 1987;Geiss et al, 2007). Further, the production of matrix metalloproteinases (MMPs) has been implicated in the resorption of the herniated NP (Doita et al, 2001). Bobechko and Hirsh (1965) and Gertzbein et al (1975) reported that herniated NP tissue is recognized as a foreign antigen that induces an autoimmune response producing inflammation.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have provided evidence for the neovascularization and infiltration of macrophages and other inflammatory cells into herniated disc tissues (12,49). In the current study, IVDs from patients with NCDH had significantly more neovascularization and granulation tissue than patients with CDH.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory and immune activation profile exhibited by a herniated disc may be distinct from that observed in the IVD degeneration and may differ further among different extents of herniation from protrusion through sequestration. Histologic evaluation of herniated disc tissue has revealed prominent infiltration of inflammatory cells, most markedly macrophages [6][7][8][9][10][11]. Various inflammatory cells, proinflammatory cytokines, antibodies, and immunoglobulins have been identified in and around herniated lumbar disc tissue.…”
Section: Introductionmentioning
confidence: 99%
“…Various inflammatory cells, proinflammatory cytokines, antibodies, and immunoglobulins have been identified in and around herniated lumbar disc tissue. Recently, it has been reported that lumbar disc tissue may be another potential immune-privileged site in the human body [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%